Food security and low-income households in the Malaysian east coast economic region: An empirical analysis - Alam, Md Mahmudul; Siwar, Chamhuri; Wahid, Abu N.M.; Abdul Talib, Basri (The Applied Regional Science Conference (ARSC) / Wiley Publishing Asia Pty Ltd, 2015)
This research, conducted to analyze the level of food security among poor and low-income households in the east coast economic region of Malaysia,uses primary data of 460 families from the E-Kasih poor households database, based on a cluster random sampling technique.Food security levels were measured using the United States Agency for International Development Household Food Insecurity Access model. Findings indicate that 52.8% of households are food secure, 23.3% mildly food insecure, 14.3% moderately food insecure, and 9.6% are severely food insecure.These findings are very important to assist policymakers to achieve Vision 2020 and the targets of Malaysian National Plans regarding food security, socioeconomic development, and the alleviation of poverty.The involvement of private sector and community-based organizations are important to combat short run, seasonal, and event-related risks, as well as for the development of appropriate mitigation and adaptation options to ensure sustainable food security at household level in Malaysia.